Narcissistic leadership and team creativity: Assessing the mediating role of information searching effort and moderating role of environmental uncertainty - Omer Azam; Syed Tahir Hussain Rizvi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The aim of this research is to assess impact of narcissistic trait of leadership on team creativity. Focus of our research will be to analyze the mediating effect of information searching effort along with the moderating effect of environmental uncertainty between narcissistic leadership and team creativity under the concept of attention-based theory and social information processing (SIP) theory. Data collection was carried out through selfadministrative questionnaires from a total of 300 respondents from IT departments and higher educational institutions that are based in the twin cities (Rawalpindi and Islamabad) of Pakistan by using simple random sampling. For testing the mediation and moderation, structural equation modeling and Preacher & Hayes regression analysis was used. Findings of this study confirm that information searching effort positively mediates between narcissistic leadership with team creativity. Also, environmental uncertainty moderates between narcissistic leadership and team creativity. This research expands the application of attention theory for enhancing the creativity of team members.
Keywords: 330; narcissistic leadership; attention theory; team creativity; information searchingeffort; environmental uncertainty; social information processing theory